2021
DOI: 10.1016/s1473-3099(21)00694-0
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 vaccine intentions in Australia

Abstract: 4 Dodd RH, Pickles K, Cvejic E, et al. Perceived public health threat a key factor for willingness to get the COVID-19 vaccine in Australia. Vaccine 2021; published online Aug 5.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…In our study, length of lockdown was clearly associated with negative mental health experiences. While the RCH Poll lacked pre-pandemic data, substantially more caregivers reported poor mental health on the K6 (average 18%) in the polls throughout the pandemic than representative Australian adult data collected pre-pandemic (8% in 2017) or during the first national lockdown (11%) 11. Notably, TPTN data found that increases in mental distress were highest for parents, tripling from 8% pre-pandemic to 24% during the pandemic 10.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, length of lockdown was clearly associated with negative mental health experiences. While the RCH Poll lacked pre-pandemic data, substantially more caregivers reported poor mental health on the K6 (average 18%) in the polls throughout the pandemic than representative Australian adult data collected pre-pandemic (8% in 2017) or during the first national lockdown (11%) 11. Notably, TPTN data found that increases in mental distress were highest for parents, tripling from 8% pre-pandemic to 24% during the pandemic 10.…”
Section: Discussionmentioning
confidence: 99%
“…While the RCH Poll lacked pre-pandemic data, substantially more caregivers reported poor mental health on the K6 (average 18%) in the polls throughout the pandemic than representative Australian adult data collected pre-pandemic (8% in 2017) or during the first national lockdown (11%). 11 Notably, TPTN data found that increases in mental distress were highest for parents, tripling from 8% pre-pandemic to 24% during the pandemic. 10 Our finding of increasing perceived negative impacts of the pandemic on children’s mental health are consistent with the emerging reviews of the published evidence.…”
Section: Discussionmentioning
confidence: 99%
“…While the RCH Poll lacked pre-pandemic data, substantially more caregivers reported poor mental health on the K6 (average 18%) in the Polls throughout the pandemic than representative Australian adult data collected pre-pandemic (8% in 2017) or during the first national lockdown (11%). 16 Notably, TPTN data found that increases in mental distress were highest for parents, tripling from 8% pre-pandemic to 24% during the pandemic. 15 Our finding of increasing perceived negative impacts of the pandemic on children’s mental health are consistent with the emerging reviews of the published evidence.…”
Section: Discussionmentioning
confidence: 99%
“…This aligns with the Australian “Pulse of the Nation” survey in which 24% of parents reported mental distress across the first months of lockdown (measured with a single item that highly correlated with the K6; Broadway et al, 2020). While the RCH Poll lacked pre‐pandemic data, substantially more caregivers reported poor mental health on the K6 in the polls than representative Australian adult data collected pre‐pandemic (8% in 2017) or during the first national lockdown (11%; Edwards et al, 2020). Our study also found a differential increase in the poor mental health of Victorian caregivers of 6.7%.…”
Section: Discussionmentioning
confidence: 99%